2016
DOI: 10.1016/j.freeradbiomed.2016.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-deficient Plasmodium berghei parasites exhibit growth delay and nuclear DNA damage

Abstract: Plasmodium parasites are exposed to endogenous and exogenous oxidative stress during their complex life cycle. To minimize oxidative damage, the parasites use glutathione (GSH) and thioredoxin (Trx) as primary antioxidants. We previously showed that disruption of the Plasmodium berghei gamma-glutamylcysteine synthetase (pbggcs-ko) or the glutathione reductase (pbgr-ko) genes resulted in a significant reduction of GSH in intraerythrocytic stages, and a defect in growth in the pbggcs-ko parasites. In this report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Data presented in our study have demonstrated that GSH treatment has favored infection and increased liver toxicity in PbA-infected mice. Although GSH represents an important antioxidant molecule in distinct tissue and organs, there are strong evidences demonstrating that species of the Plasmodium genus use GSH as a substrate for their reproduction in the vertebrate host [ 35 37 ]. Our results are in agreement with these reports since GSH treatment has induced a fast increase in parasitemia values; also, it has decreased animal survival in the PbA-infected group.…”
Section: Discussionmentioning
confidence: 99%
“…Data presented in our study have demonstrated that GSH treatment has favored infection and increased liver toxicity in PbA-infected mice. Although GSH represents an important antioxidant molecule in distinct tissue and organs, there are strong evidences demonstrating that species of the Plasmodium genus use GSH as a substrate for their reproduction in the vertebrate host [ 35 37 ]. Our results are in agreement with these reports since GSH treatment has induced a fast increase in parasitemia values; also, it has decreased animal survival in the PbA-infected group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, T. gondii uses the thiol-reduction system, including glutathione, Trx, glutaredoxin, and specific reductases, to resist oxidative damage. These enzymes, which are associated with the antioxidant system, play essential roles during parasite survival and infection ( Padín-Irizarry et al, 2016 ). However, it remains unclear whether other unidentified genes are involved in the resistance to host ROS ( Boczoń, 2002 ).…”
Section: Introductionmentioning
confidence: 99%